2012
DOI: 10.1111/j.1600-0706.2012.20805.x
|View full text |Cite
|
Sign up to set email alerts
|

How the aphids got their spots: predation drives self‐organization of aphid colonies in a patchy habitat

Abstract: Using a 30 day time series of aphid Aphis helianthi and coccinellid counts on 107 mapped racemes of Yucca glauca, we demonstrate progressive, predation-induced self-organization of aphid colonies on individual racemes into extremely low and extremely high population sizes. This was driven by a two-attractor structure of density dependence that developed only in the presence of coccinellid predators. Foraging movements of the coccinellids among plants produced a power law relationship (average power  0.142) be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 34 publications
(48 reference statements)
0
18
0
Order By: Relevance
“…This reinforces the need for an analysis of the slopes of density response curves, together with theoretical work to determine what levels of depensatory density dependence may be ecologically significant in host-parasitoid systems, and whether the concept of 'density independence' needs defining (ecologically rather than statistically). It must be emphasized that the relevance of these findings is primarily to questions of spatial pattern formation rather than temporal dynamics (Hassell 2000;Kummel, Brown & Bruder 2013), and it is important to note that spatial density dependence is not simply linked to demographic density dependence (Stewart-Oaten & Murdoch 1990). The predominance of compensatory spatial density dependence should promote spatial homogeneity in host densities, subject to other factors such as the possibility of over-compensation (cf.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This reinforces the need for an analysis of the slopes of density response curves, together with theoretical work to determine what levels of depensatory density dependence may be ecologically significant in host-parasitoid systems, and whether the concept of 'density independence' needs defining (ecologically rather than statistically). It must be emphasized that the relevance of these findings is primarily to questions of spatial pattern formation rather than temporal dynamics (Hassell 2000;Kummel, Brown & Bruder 2013), and it is important to note that spatial density dependence is not simply linked to demographic density dependence (Stewart-Oaten & Murdoch 1990). The predominance of compensatory spatial density dependence should promote spatial homogeneity in host densities, subject to other factors such as the possibility of over-compensation (cf.…”
Section: Discussionmentioning
confidence: 97%
“…It must be emphasized that the relevance of these findings is primarily to questions of spatial pattern formation rather than temporal dynamics (Hassell ; Kummel, Brown & Bruder ), and it is important to note that spatial density dependence is not simply linked to demographic density dependence (Stewart‐Oaten & Murdoch ). The predominance of compensatory spatial density dependence should promote spatial homogeneity in host densities, subject to other factors such as the possibility of over‐compensation (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Herbivore biomass was described by logistic growth, predation, and density‐independent mortality. We assumed a type II functional response as found in other ladybeetles and aphid species (Kummel et al., 2013; Pervez & Omkar, 2005). {leftHi,t+1=Hi,t+gHHi,tkHHi,tkHePHi,tPi,tHi,t+H0mH,i,tHi,tleftPi,t+1=Pi,t+aPePHi,tPi,tHi,t+H0mP,i,tPi,t …”
Section: Methodsmentioning
confidence: 99%
“…These behaviors promote the aggregation of ladybeetles at patches with more aphids and create a positive relationship between aphid densities and the change in ladybeetle densities. However, this aggregation is not always found in the field, as a number of studies have found that the spatial distribution of ladybeetles at large scales does not track the distribution of aphids very well (Hacker & Bertness, 1995; Krivan, 2008; Kummel, Brown, & Bruder, 2013). Therefore, in ladybeetle–aphid systems, it seems that both the effect of the predator on the prey and the effect of the prey on the predator potentially vary with spatial scale.…”
Section: Introductionmentioning
confidence: 99%
“…Table 3: The comparison of predator persistence and extinction between Model (1) and Model (7). and the recent experimental work of immobile Aphids and Coccinellids by [43], we formulate a two patch prey-predator model (1) with the following assumptions: (a) In the absence of dispersal the model reduced to the two uncoupled Rosenzweig-MacArthur prey-predator single patch models (2); (b) Prey is immobile; and (c) Predator foraging movements are driven by the strength of prey-predator interaction. We provide basic dynamical properties such positivity and boundedness of our model in Theorem 2.1.…”
Section: Extinction Of Predator Simulations Suggestions (See the Yellmentioning
confidence: 99%